Exploring The Effectiveness of Digital Educational Supervision in Indonesian Overseas Schools: a Phenomenological Study - Tumin (Institut Agama Islam An-Nawawi Purworejo, 2025)
Educational supervision plays a crucial role in maintaining teaching quality and ensuring compliance with academic standards. However, overseas Indonesian schools often receive less intensive supervision compared to domestic institutions. This study explores the supervision and control functions within the educational management system at Sekolah Indonesia Luar Negeri (SILN) Jeddah. Using a qualitative field research design, data were collected through interviews, observations, and document analysis to examine the implementation of supervisory practices. The findings reveal that while the supervision system at SILN Jeddah is relatively structured and functional, limited teacher availability due to workload presents significant challenges. In response, the school has integrated digital tools such as video-based supervision and online meetings, enhancing efficiency and flexibility in supervision. This study contributes to the field of educational management by highlighting the potential of technology-driven supervision in international school contexts and emphasizing the importance of adaptive leadership. The results suggest that digital innovation in supervision can help improve teacher performance and student learning outcomes.